Synthesis, characterization and apoptotic activity of quinazolinone Schiff base derivatives toward MCF-7 cells via intrinsic and extrinsic apoptosis pathways - Zahedifard, M.; Faraj, F.L.; Paydar, M.; Looi, C.Y.; Hajrezaei, M.; Hasanpourghadi, M.; Kamalidehghan, B.; Majid, N.A.; Ali, H.M.; Abdulla, M.A. (Nature Publishing Group, 2015)
The current study investigated the cytotoxic effect of 3-(5-chloro-2-hydroxybenzylideneamino)-2-(5-chloro-2-hydroxyphenyl)-2,3-dihydroquinazolin-41(H)-one (A) and 3-(5-nitro-2-hydroxybenzylideneamino)-2-(5-nitro-2-hydroxyphenyl)-2,3-dihydroquinazolin-4(1H)-one (B) on MCF-7, MDA-MB-231, MCF-10A and WRL-68 cells. The mechanism involved in apoptosis was assessed to evaluate the possible pathways induced by compound A and B. MTT assay results using A and B showed significant inhibition of MCF-7 cell viability, with IC 50 values of 3.27±0.171 and 4.36±0.219μg/mL, respectively, after a 72hour treatment period. Compound A and B did not demonstrate significant cytotoxic effects towards MDA-MB-231, WRL-68 and MCF-10A cells. Acute toxicity tests also revealed an absence of toxic effects on mice. Fluorescent microscopic studies confirmed distinct morphological changes (membrane blebbing and chromosome condensation) corresponding to typical apoptotic features in treated MCF-7 cells. Using Cellomics High Content Screening (HCS), we found that compound A and B could trigger the release of cytochrome c from mitochondria to the cytosol. The release of cytochrome c activated the expression of caspases-9 and then stimulated downstream executioner caspase-3/7. In addition, caspase-8 showed remarkable activity, followed by inhibition of NF-κ B activation in A-and B-treated MCF-7 cells. The results indicated that A and B could induce apoptosis via a mechanism that involves either extrinsic or intrinsic pathways.